2021
DOI: 10.1007/s00586-020-06701-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for correction rate in severe idiopathic scoliosis (Cobb angle ≥ 90°): an analysis of 128 patients

Abstract: Purpose Knowledge on the factors affecting the correction rate (CR) aids in the surgical planning among severe idiopathic scoliosis (IS) patients. This study aimed to investigate the independent factors affecting CR among patients with severe IS (Cobb angle ≥ 90°) who underwent single-staged posterior spinal fusion (PSF). Methods We retrospectively reviewed 128 severe IS patients who underwent single-staged PSF. Factors including age, height, weight, body mass index, Risser sign, Lenke subtypes, preoperative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…[ 28 ] After that, several other studies reported very good results (around 55%–60% of major curve correction rate) with one-stage PSF. [ 1 21 35 23 24 26 27 30 31 32 33 ] This is in line with the current literature. In fact, most of the studies on the surgical treatment of severe AIS show contained correction rate values, often lower than 60% regardless of the technique used:[ 2 3 4 5 6 7 8 9 10 ] in these cases, the aim was not to maximize correction but to obtain an acceptable balance of the spine and save levels of fusion.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…[ 28 ] After that, several other studies reported very good results (around 55%–60% of major curve correction rate) with one-stage PSF. [ 1 21 35 23 24 26 27 30 31 32 33 ] This is in line with the current literature. In fact, most of the studies on the surgical treatment of severe AIS show contained correction rate values, often lower than 60% regardless of the technique used:[ 2 3 4 5 6 7 8 9 10 ] in these cases, the aim was not to maximize correction but to obtain an acceptable balance of the spine and save levels of fusion.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 1337 studies were found through electronic search; after screening, 14 studies (1 prospective cohort study,[ 23 ] 3 retrospective comparative studies,[ 24 25 26 ] 1 retrospective cohort study,[ 27 ] 6 retrospective studies,[ 28 29 30 31 32 33 ] 1 prospective CS,[ 34 ] and 2 retrospective CS[ 1 21 ]) were included. [ 1 21 23 24 25 26 27 28 30 31 33 34 ] The quality of the papers was good in 13 cases[ 1 21 23 24 25 26 27 28 30 31 33 ] and fair in 1 case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations